The cyclical behavior of equilibrium unemployment and vacancies revisited - Marcus Hagedorn; Iourii Manovskii (European Central Bank (ECB), 2008)
Recently, a number of authors have argued that the standard search model cannot generate the observed business-cycle-frequency fluctuations in unemployment and job vacancies, given shocks of a plausible magnitude. We use data on the cost of vacancy creation and cyclicality of wages to identify the two key parameters of the model - the value of non-market activity and the bargaining weights. Our calibration implies that the model is, in fact, consistent with the data.
Keywords: E24; E32; J41; J63; J64; 330; business cycles; labor markets; Matching; Search; Arbeitslosigkeit; Konjunktur; Urlaub; Suchtheorie; USA